International finance and development - Ocampo, Jose Antonio (ed.); Kregel, Jan (ed.); Griffith-Jones, Stephany (ed.) (London, 2007)
International Finance and Development offers a comprehensive survey of the major financing issues influencing economic development since the historic Monterrey Consensus of the International Conference on Financing for Development in 2002. As most recent international private capital flows have been unlikely to significantly enhance new productive investments in the developing countries, it is necessary to design appropriate mechanisms to ensure they contribute to development. However, recent trends in official development financing offer some grounds for optimism, although much more needs to be done. External debt problems of many developing countries, especially the least developed countries, seem likely to continue to constrain their prospects for development. The final part on systemic issues highlights new concerns and the modest progress in ensuring that the international monetary and financial system better serves economic growth and development throughout the world, especially in the developing countries.
Keywords: International finance